2005
DOI: 10.2960/j.v35.m516
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons of Trawl and Longline Catches of Deepwater Elasmobranchs West and North of Ireland

Abstract: A comparison was made between catches from deepwater trawl and longline surveys (1993)(1994)(1995)(1996)(1997)(1998)(1999)(2000) in the Northeast Atlantic. Longline catches were dominated by elasmobranchs, particularly squalid sharks and species numbers were low. Trawl catches had higher species numbers, with more teleosts, though elasmobranchs were still an important component. Species composition of the catch was depth dependent. Comparative trawl and longline surveys of the eastern and southern slopes of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 13 publications
2
24
1
Order By: Relevance
“…Hydrolagus affinis has been observed visiting baits at depths of 2020 m in the north Atlantic Ocean (Priede et al 1994), and several species have been caught on baited hooks, confirming scavenging behaviour, e.g. H. affinis (Forster 1964), Hydrolagus pallidus (Marques & Porteiro 2000) and C. monstrosa (Clarke et al 2005). Although the diet of chimaeras may be predominantly benthic fauna, scavenging behaviour suggests they retain a degree of opportunism.…”
Section: Discussionmentioning
confidence: 86%
“…Hydrolagus affinis has been observed visiting baits at depths of 2020 m in the north Atlantic Ocean (Priede et al 1994), and several species have been caught on baited hooks, confirming scavenging behaviour, e.g. H. affinis (Forster 1964), Hydrolagus pallidus (Marques & Porteiro 2000) and C. monstrosa (Clarke et al 2005). Although the diet of chimaeras may be predominantly benthic fauna, scavenging behaviour suggests they retain a degree of opportunism.…”
Section: Discussionmentioning
confidence: 86%
“…Most studies on bycatch and discards of elasmobranchs consider trawl and longline fisheries (Carbonell et al, 2003;Clarke et al, 2005;Coelho and Erzini, 2008;Megalofonou et al, 2005;Stobutzki et al, 2002). Erzini et al (2002) studied discards from the most important fisheries in southern coast of Portugal and found that, despite a great diversity of species caught, including seven chondrichthyan species, trammel nets were those with lower discards.…”
Section: Discussionmentioning
confidence: 97%
“…Sexual dimorphism, or differences in mortality between sexes, could explain the biased sex ratio in the adults (Rago et al, 1998). Unequal sex ratios are quite common in longlines catches (Wirtz and Morato, 2001) because, although small fish taking bait from longlines may be scared away by larger fish (Clarke et al, 2005), the use of smaller hooks does not lead to catching small specimens (Veríssimo et al, 2003). Additionally, a higher natural mortality for males could have caused the biased sex ratio.…”
Section: Discussionmentioning
confidence: 98%